Idealizations of the Kleinhaus: On the Typology of the Small Single-Family House in Germany, 1920s–1960s. Issue 1 (25th October 2018) - Lorbek, Maja
Abstract : In the 20th century, detached single-family houses proliferated in Germany. Continued publication of built houses as idealised, model homes in magazines for non-professional housebuilders contributed to the popularity of detached single-family housing, influenced the architecture of single-family homes, and contributed to shaping the culture of habitation. Through their customer magazines, aimed at non-professional housebuilders, German building societies played a crucial role in the constitution of self-provided detached housing. With a focus on the Kleinhaus (small house), this paper uses mediated representations of built houses to trace the evolution of single-family houses in Germany from the 1920s to the 1960s, as they were represented in Mein Eigenheim, a customer magazine of the Wüstenrot — Gesellschaft der Freunde (GdF) building society. During the Weimar era (1919–1933), the GdF magazine highlighted the affordability and modest size of the Kleinhaus . Following the financial crisis of the late 1920s and the rise of Nazism, the economy of self-sufficiency, centred on vegetable gardens, became a popular theme. During the 1950s, under the influence of increasing material progress, the significance of the Kleinhaus changed. The gardens lost their economic function and became extended living spaces. In the late 1950s, the Kleinhaus lost its dominant position on the housing market, with the emergence of new building types such as the bungalow and larger homes with two full storeys, which better catered to the desires of an affluent and increasingly individualised society.